Predictive factors and comparative analysis of surgical vs. endovascular treatment for spinal dural arteriovenous fistulas: a 22-year experience at a neurovascular and spine center - Mido Max Hijazi; Andreas Filis; Penelope Felgenhauer; Kay Engellandt; Sergio M.F. Romualdo; Dino Podlesek; Tareq A. Juratli; Ilker Y. Eyüpoglu (Brain and Spine)
Background: Spinal dural arteriovenous fistula (SDAVF) is a rare disease with insidious clinical manifestations that can often be overlooked on initial examination. Our aim was to identify predictive factors associated with favorable long-term outcomes and to compare the clinical results between surgical and endovascular treatment. Methods: A retrospective chart review was conducted of 81 patients with SDAVF who underwent either surgical (n = 70, 86.4 %) or endovascular (n = 11, 13.6 %) treatment at our hospital between 2002 and 2023, with a mean follow-up duration of 22.4 months. Results: A significantly greater proportion of surgical (S) patients (45/70, 64.3 %) showed improvement in the modified Aminoff and Logue Scale (mALS) between admission and last follow-up compared to endovascular (E) patients (3/11, 27.3 %; p = 0.043). There were no significant differences between the two groups over the clinical course (preoperative, postoperative, first, second, and third follow-up) in terms of mALS, American Spinal Injury Association Motor Score (ASIA-MS), back pain, or sensory disturbances. Incomplete or failed fistula closure occurred significantly more frequently in the endovascular group than in the surgical group (S: 3/70, 4.3 % vs. E: 5/11, 45.5 %, p < 0.001). The time interval between MRI-based diagnosis and treatment was identified as an independent predictor of long-term mALS improvement in the multivariate logistic regression analysis (0.978 (0.959–0.997), p = 0.026). Conclusions: Surgical treatment of SDAVF is generally safe and effective and shows superior outcomes compared to endovascular treatment; however, endovascular therapy remains an important option in special cases. Moreover, the time interval between MRI-based diagnosis and surgical or endovascular treatment plays a critical role in determining long-term clinical outcomes of SDAVF patients.